THE CHOICE OF COULORS IN THE DIDACTIC PICTURE APPLIED IN TEACHING ELECTRONICS - KRUPA, Krzysztof (Trends in education, 2009)
The article analyses the physiological foundations of colour perception, the influence of colours on human psyche and the possibility of using a colourful visual means in technology teaching and in particular the didactic drawing, applied in teaching electronics.
Keywords: colors; perception; teaching; drawing; electronics.